Enhancing Students' Writing Skills through Writing Techniques and Mastery of Different Discourse Markers - Suryadi Suryadi; Fajar Erlangga (AL-ISHLAH: Jurnal Pendidikan, 2025)
Effective writing instruction requires innovative techniques to improve coherence and fluency, particularly among second-language learners. Reflective Learning Portfolio (RLP) emphasizes reflective practice in learning, while Dialogue Journal Writing (DJW) fosters community, enhances interactions, and builds self-awareness. Despite their individual merits, the integrated effect of these reflective techniques alongside discourse markers on students' writing proficiency remains understudied. This research employed a quantitative, quasi-experimental methodology with a non-equivalent control group using a two-way factorial design. From a total cohort of 1000 students at a State Islamic Senior High School in Serang Regency, Indonesia, a random sample of 200 participants was selected. Students were grouped based on treatment (RLP and DJW) and proficiency levels in discourse marker usage (high, medium, low). Findings revealed three key outcomes: (1) significant differences in writing skills between students instructed with RLP and those using DJW; (2) notable variations in writing proficiency correlated with students’ ability to use discourse markers, categorized as high, medium, and low proficiency; and (3) a significant interaction effect between writing techniques and discourse marker proficiency, suggesting the combined influence substantially impacts writing skills. This study uniquely integrates reflective writing techniques and discourse marker training, highlighting their combined role in enhancing structural coherence and promoting metacognitive growth in student writing. It demonstrates the value of explicitly teaching discourse markers within reflective instructional contexts, providing valuable insights into effective pedagogical strategies for second language writing instruction.